Pengaruh service quality dan staff behaviour terhadap brand loyalty TIKI di Jakarta Utara: Customer satisfaction sebagai variabel mediasi - Surya, Rendy (Jurnal Manajemen Bisnis dan Kewirausahaan, 2017)
The purposes of this study are: First, to explore the effect of service quality on brand loyalty. Second, to explore the effect of staff behaviour on brand loyalty. Third, to explore the effect of service quality on customer satisfaction. Fourth, to explore the effect of customer satisfaction on brand loyalty. Fifth, to find out if customer satisfaction can mediate service quality toward brand loyalty. The populations of this research are all TIKI’s customers in Jakarta. The samples of this research are collected from TIKI’s customers in North Jakarta. The method of data collection was conducted by distributing questionnaires to 200 respondents. The technique of data analysis used in this study was a Partial Least Square and indirect effect test for mediation variables as an example of the hypotheses. The results are: first, the relationship between service quality has a significant and positive effect toward brand loyalty; second, the relationship between staff behaviour has a significant and positive effect toward brand loyalty; third, the relationship between service quality has a significant and positive effect toward customer satisfaction; forth, customer satisfaction has a significant and positive effect toward brand loyalty; fifth, customer satisfaction will mediate the effect between service quality on brand loyalty.